2019
DOI: 10.1371/journal.pone.0223971
|View full text |Cite|
|
Sign up to set email alerts
|

Clinicopathologic and prognostic significance of tumor-associated macrophages in patients with hepatocellular carcinoma: A meta-analysis

Abstract: PurposeTumor-associated macrophages (TAMs) deserve more focus because of its clinicopathologic and prognostic roles in solid tumors. However, the prognostic value of TAMs in patients with hepatocellular carcinoma (HCC) is still controversial. We performed a meta-analysis to resolve the issue.MethodsWe selected relevant studies from the Cochrane Library, Embase and PubMed databases. The hazard ratios (HRs) and 95% confidence intervals (CIs) were calculated employing fixed-effect or random-effect models dependin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 55 publications
(107 reference statements)
0
26
1
Order By: Relevance
“…25 In general, TAMs exhibit the M2 phenotype, and their infiltration is known to be associated with poor prognosis in HCC. 9,11,26 However, the…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 In general, TAMs exhibit the M2 phenotype, and their infiltration is known to be associated with poor prognosis in HCC. 9,11,26 However, the…”
Section: Discussionmentioning
confidence: 99%
“…1,9 Moreover, the infiltration of various immune cells, such as tumor-associated macrophages (TAMs), leads to an immunosuppressive microenvironment. 10,11 However, only 14-18% of the patients who receive pembrolizumab or nivolumab monotherapy demonstrate objective tumor responses. [12][13][14] Moreover, unlike that in other solid tumors, no significant association was identified between tumor cell programmed cell death ligand 1 (PD-L1) expression and anti-PD-1 responses in HCC, as reported by the Keynote-224 and CheckMate-040 studies.…”
Section: Introductionmentioning
confidence: 99%
“…[ 25 ] CD68 is the most extensively used marker of macrophages and is used to identify overall TAMs. [ 26 , 27 ] Whereas M1 and M2 subsets of TAMs are identified according to polarization. [ 28 ] M1 TAMs are known to induce inflammation and play a crucial role in anti-tumor activity.…”
Section: Discussionmentioning
confidence: 99%
“…In the present meta-analysis, the results showed the prognostic of CD68+ TAMs in IT was also not significant for OS in patients with NPC, which was in accordance with the results of SCCHN. [ 34 ] Referring relevant meta-analyses on TAMs, [ 10 , 27 , 35 , 36 ] I defined TAMs as CD68+ as the overall cell population and CD163+, CD68+CCL18+, and CD206+ as M2-like TAMs. The tissue distribution (IT and/or TS) was used to further stratify the location of diverse subsets of TAMs.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed in the previous section, the differentiation of TAMs in the TME can contribute for their pro-tumor characteristics [42, 85]. In this regard, several meta-analysis have clearly demonstrated that an increase in the number of TAMs is generally associated with poor prognosis [86, 87]. During cancer progression, several mechanisms have been identified to overcome antitumor response by TAMs including the secretion of prostaglandin E2 [88], the immunosuppressive cytokine IL-10 [89], the angiogenic factors such as IL-1β, that through upregulation of HIF-1α protein increases vascular endothelial growth factor (VEGF) secretion [90], VEGF [91], endothelin-2 [92], and epidermal growth factor family ligands [93].…”
Section: The Immune System and Cancermentioning
confidence: 99%